Hypoxia Pathway Proteins in Normal and Malignant Hematopoiesis - Ben Wielockx; Tatyana Grinenko; Peter Mirtschink; Triantafyllos Chavakis (Cells, 2019)
The regulation of oxygen (O2) levels is crucial in embryogenesis and adult life, as O2 controls a multitude of key cellular functions. Low oxygen levels (hypoxia) are relevant for tissue physiology as they are integral to adequate metabolism regulation and cell fate. Hence, the hypoxia response is of utmost importance for cell, organ and organism function and is dependent on the hypoxia-inducible factor (HIF) pathway. HIF pathway activity is strictly regulated by the family of oxygen-sensitive HIF prolyl hydroxylase domain (PHD) proteins. Physiologic hypoxia is a hallmark of the hematopoietic stem cell (HSC) niche in the bone marrow. This niche facilitates HSC quiescence and survival. The present review focuses on current knowledge and the many open questions regarding the impact of PHDs/HIFs and other proteins of the hypoxia pathway on the HSC niche and on normal and malignant hematopoiesis.